Utilizing digital marketing to improve the performance of MSMEs in Kraton District, Yogyakarta - Alteza, Muniya; Rahmawaty, Penny; Hidayati, Lina Nur; Darmawati, Arum (Universitas Muhammadiyah Magelang, 2025)
This community service activity aims to enhance the marketing reach and performance of MSMEs in Kraton District, Yogyakarta, through the utilization of digital marketing. The activities were conducted through training and mentoring. The methods used included lectures, discussions, and practical exercises. Lectures were delivered to introduce digital marketing concepts and tools. Practical exercises involved the application of digital marketing through the creation of online shop accounts on marketplaces and Google Business Profiles. The evaluation results showed an increase, with 32% of MSMEs now having online shop accounts; 58% of MSMEs having Google Business Profiles; a 15% increase in sales post-digital marketing implementation; and a 10% increase in visits to MSMEs that have Google Business Profiles.